Estimación del potencial geotérmico de baja entalpía para la ciudad de Bogotá y la Sabana de Bogotá usando bombas de calor de agua subterránea (2020)
This present work shows the results on a regional scale of some municipalities of the Sabana de Bogotá for the estimation of the low enthalpy geothermal potential using groundwater heat exchangers. The aim of this study is to show and identify the potential areas for the implementation of a renewable energy project that will be very useful for the communities. All the estimations were done using a geographic information system called ArcGIS and using the static level data from wells acquired by the CAR (Corporación autonoma regional). The potential of the study area is shown in meters to be drilled, because this is one of the most expensive components of a system of this type. To evaluate this potential, the regional static level and the groundwater drawdown caused by the pumping water to the heat pump were used. The final average of the meters to be drilled in the Sabana de Bogotá presents a range between 70 to 140 meters.